The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.jval.2015.09.877
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Of Overall Costs Between Alprostadil And Limb Amputation In Patients Affected By Peripheral Arterial Disease Stages Iii And Iv In Mexico

Abstract: Sixteen economic analyses were included; all studies used decision-tree structures to model acute prophylaxis, and 13 included a chronic-phase Markov module to capture long-term complications and recurrent VTE events. The model structures generally captured the important events needed to accurately estimate differences in costs and outcomes between different treatment strategies. Eleven studies included rivaroxaban, 9 studies included dabigatran, 3 studies included apixaban, and no studies included edoxaban. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[16] Alprostadil has extensive physiological and pharmacological effects, including vasodilation, inhibits platelet aggregation, promote erythrocyte deformation, thus improving microcirculation. Research [17,18] has also shown that alprostadil can stabilize the cell membrane, lysosomes and reduce the release of harmful cytokines, increasing renal blood flow, reducing the damage of the contrast agent to the blood vessel.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Alprostadil has extensive physiological and pharmacological effects, including vasodilation, inhibits platelet aggregation, promote erythrocyte deformation, thus improving microcirculation. Research [17,18] has also shown that alprostadil can stabilize the cell membrane, lysosomes and reduce the release of harmful cytokines, increasing renal blood flow, reducing the damage of the contrast agent to the blood vessel.…”
Section: Introductionmentioning
confidence: 99%